Safety Factor of Timber Bolted-Connection Designed with SNI-5 (2002) - Awaludin, Ali (Institut Teknologi Bandung, 2005)
Abstract. This paper study the safety factor of timber connection designed with PKKI NI-5 (2002). Johansen yield model is used to evaluate the nominal design value of single bolted connection. Double-shear bolted connection, with the side members and the main member from wood, is chosen for this study. A comparison study of safety factor between SNI-5 (2002) and NDS for timber construction of U.S (1997) is also conducted. Finally, the safety factor is analyzed for both directions parallel and perpendicular to wood grain of four possible yield modes. From the study, both SNI-5 (2002) and NDS (1997) use higher safety factor for bolted connection sustaining load perpendicular to grain than that sustaining load parallel to grain. Smaller safety factor is used in bothcodes when the plastic hinge of bolt is created such as the yield modes IIIs and IV. However, in this case, the safety factor of NDS is significantly much higher than that of SNI-5 (2002).Abstrak. Analisis angka aman sambungan baut yang dirancang dengan SNI-5 (2002) dibahas pada tulisan ini. Tahanan lateral sambungan baut dianalisis berdasarkan teori model kelelehan yang diusulkan oleh Johansen (1949). Sambungan baut dua irisan dipilih sebagai contoh kasus. Analisis angka aman sambungan yang dirancang dengan SNI-5 (2002) juga dibandingkan dengan angka aman pada peraturan NDS (1997). Selain itu, analisis angka aman juga diteliti untuk sudut gaya sejajar dan tegak lurus serat, serta berdasarkan pada moda kelelehan sambungan. Berdasarkan hasil analisis, baik SNI-5 (2002) dan NDS (1997) menggunakan angka aman yang lebih besar pada sambungan dengan arah gaya tegak lurus terhadap serat kayu dari pada angka aman pada sambungan dengan arah gaya sejajar serat kayu. Angka aman yang lebih kecil digunakan pada kedua peraturan di atas apabila bentuk kelelehan sambungan disebabkan oleh terbentuknya sendi plastis pada baut (moda kelelehan IIIs dan IV). Walaupun demikian, secara umum angka aman yang digunakan oleh SNI-5 (2002) jauh lebih kecil dari pada angka aman yang dipergunakan oleh NDS (1997).